1991
DOI: 10.1172/jci115135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cocaine on excitation-contraction coupling of aortic smooth muscle from the ferret.

Abstract: The mechanism by which cocaine alters vascular tone is not fully understood. We determined the effects of cocaine on excitation-contraction coupling of isolated ferret aorta. Cocaine in concentrations < 10-4 M caused a contractile response in a dose-dependent manner. The response of control muscle was significantly larger than that in muscle from ferrets pretreated with reserpine. Cocaine-induced contraction was not affected by endothelial factors, but was significantly inhibited by prazosin 10-7 M pretreatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 32 publications
0
24
0
3
Order By: Relevance
“…Several mechanisms contribute to the hemodynamic response to cocaine in adults. On the one hand, cocaine increases central sympathetic transmission and blocks the reuptake of norepinephrine, potentiating the myocardial contractile and vasoconstrictor ef fect of this catecholamine, which increases arterial pressure [26][27][28][29]. On the other hand, cocaine, as a local anesthetic, inhibits intracel lular calcium availability, resulting in de pressed myocardial contractility, vasodila tion, and decreased arterial pressure [28,29], In adults, the pressor response dominates over the depressor response because the sym pathetic nervous system is fully functional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms contribute to the hemodynamic response to cocaine in adults. On the one hand, cocaine increases central sympathetic transmission and blocks the reuptake of norepinephrine, potentiating the myocardial contractile and vasoconstrictor ef fect of this catecholamine, which increases arterial pressure [26][27][28][29]. On the other hand, cocaine, as a local anesthetic, inhibits intracel lular calcium availability, resulting in de pressed myocardial contractility, vasodila tion, and decreased arterial pressure [28,29], In adults, the pressor response dominates over the depressor response because the sym pathetic nervous system is fully functional.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, cocaine increases central sympathetic transmission and blocks the reuptake of norepinephrine, potentiating the myocardial contractile and vasoconstrictor ef fect of this catecholamine, which increases arterial pressure [26][27][28][29]. On the other hand, cocaine, as a local anesthetic, inhibits intracel lular calcium availability, resulting in de pressed myocardial contractility, vasodila tion, and decreased arterial pressure [28,29], In adults, the pressor response dominates over the depressor response because the sym pathetic nervous system is fully functional. We speculate that the pressor effect in the newborn is less than in the adult because the sympathetic nervous system is immature, in that less catecholamine is present in the syn aptic cleft and peripheral vascular receptors are less sensitive to the neurotransmitter [19].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to sympathomimetic effects, blockade of cardiomyocyte sodium channels acts as a class I antiarrhythmic agent or local anesthetic [13], and blockade of both the cardiomyocyte sodium and potassium channels has been shown to depress cardiovascular parameters by decreasing myocardial contractility, causing arrhythmia, and decreasing left ventricular ejection fraction [10,[14][15][16]. Recent research also suggests the potential for cocaine to disrupt excitationcontraction coupling via prevention of calsequestrin polymerization in the sarcoplasmic reticulum and altered storage and release of calcium with arrhythmogenic effects [17].…”
Section: Cardiomyocytesmentioning
confidence: 99%
“…We have shown that the contractile response of ferret muscles is inhibited when they are pretreated with reserpine ( Fig. (1)) [34]. This happens because reserpine depletes the synaptic vesicles of norepinephrine.…”
Section: Effect On Vascular Resistancementioning
confidence: 85%